Transparency, Corruption, and Democratic Institutions - Hubbs, Graham (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2014)
This essay examines some of the institutional arrangements that underlie corruption in democracy. It begins with a discussion of institutions as such, elaborating and extending some of John Searle’s remarks on the topic. It then turns to an examination of specifically democratic institutions; it draws here on Joshua Cohen’s recent Rousseau: A Free Community of Equals. One of the central concerns of Cohen’s Rousseau is how to arrange civic institutions so that they are able to perform their public functions without being easily abused by their members for individual gain. The view that Cohen sketches on behalf of Rousseau offers a clear framework for articulating institutional corruption in democracy. With this account of democratic institutions in place, the essay turns the discussion to the role of transparency in deterring institutional corruption. The basic thought here is perhaps unsurprising: to ensure that a democratic institution is serving its public function and not being manipulated for self-interested gain, its activities must be subject to public scrutiny, and so these activities must be transparent to the public. Saying this makes the role of transparency in a well-functioning democracy clear, but it does not settle how transparency is to be realized. The essay argues that transparency can be realized in a democracy only by an extra-governmental institution that has several of the familiar features of the press. If this is correct, it follows that in its design and in many, though not all, of its activities, WikiLeaks provides a contemporary example of such an institution.